2010
DOI: 10.1002/elan.200900346
|View full text |Cite
|
Sign up to set email alerts
|

Boron‐Doped Diamond Electrode Coupled to Liquid Chromatography: Application to Simultaneous Determination of Benzodiazepines

Abstract: The applicability of boron-doped diamond (BDD) as a working electrode in an amperometric cell, coupled to HPLC, was demonstrated, for determining benzodiazepines in pharmaceutical preparations. The separation of the benzodiazepines was achieved using a Waters XTerra RP18 column (250 Â 4.6 mm, 5 mm) with a mobile phase sodium phosphate (pH 3.5; 0.10 mol L . The measurements were performed in a system 871 Advanced Bioscan (Metrohm) with a BDD (8000 ppm) adapted to the thin layer mode cell. Stainless steel and pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 30 publications
0
14
0
1
Order By: Relevance
“…Several types of laboratory-made flow-through detection cells have been designed for this purpose mostly with electrodes in wall-jet [10][11][12][13] or thinlayer [14,15] arrangements. Further, commercial thinlayer flow cells (Bioanalytical System and ESA, both USA) were adapted for BDD electrodes [16,17]. In our laboratory, a pen-type BDD disk electrode was designed [2] and successfully used for voltammetric determination of 2-aminobiphenyl (2-AB), 3-aminobiphenyl (3-AB), and 4-aminobiphenyl (4-AB) [18], 3-nitrofluoranthene and 3-aminofluoranthene [19], and phenolic compounds in foods [13]; in the latter study this electrode was also employed in laboratory-made wall-jet amperometric detection cell.…”
Section: Introductionmentioning
confidence: 99%
“…Several types of laboratory-made flow-through detection cells have been designed for this purpose mostly with electrodes in wall-jet [10][11][12][13] or thinlayer [14,15] arrangements. Further, commercial thinlayer flow cells (Bioanalytical System and ESA, both USA) were adapted for BDD electrodes [16,17]. In our laboratory, a pen-type BDD disk electrode was designed [2] and successfully used for voltammetric determination of 2-aminobiphenyl (2-AB), 3-aminobiphenyl (3-AB), and 4-aminobiphenyl (4-AB) [18], 3-nitrofluoranthene and 3-aminofluoranthene [19], and phenolic compounds in foods [13]; in the latter study this electrode was also employed in laboratory-made wall-jet amperometric detection cell.…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally, in many cases the CPT is preceded by an APT to clean the BDDE surface, oxidizing any strongly adsorbed organic contaminant . For example, the electroanalytical determination of the herbicide picloram was carried out using a CPT‐BDDE, whose pretreatment was always preceded by an APT; the CPT or APT involved polarizations at −2.0 V or +2.0 vs .…”
Section: Electroanalytical Applications Of Electrochemically Pretreatmentioning
confidence: 99%
“…Both Hg and carbon based working electrodes have been employed successfully for benzodiazepine determination in complex samples such as blood, milk and tissue. More recently, Martins et al [54] have reported on the determination of diazepam, clonazepam, flunitrazepam and nitrazepam using boron doped diamond electrode (BDDE), as part of a liquid chromatographic system. Cyclic voltammetry was employed to investigate the electrochemical behaviour of the four benzodiazepines at the BDDE in 0.1 M phosphate buffer at pH 3.5, 6.0 and 8.0 with the optimum response obtained at pH 3.5.…”
Section: Liquid Chromatography Electrochemical Detection Of Benzodiazmentioning
confidence: 99%